A barrier film for a fiber cartridge, a recycled composite material, and a method of manufacturing a barrier film
Patent Information
- Application Number
- CN202611387562.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-08
- Publication Date
- 2026-11-03
AI Technical Summary
The existing combination structure of fiber trays and barrier membranes makes it difficult to achieve clean separation during the recycling process, which affects recycling efficiency, and the barrier performance is insufficient to protect high-requirement products.
A heat-sealing layer is made of a blend of first-metallocene polyethylene and second-metallocene polyethylene, combined with maleic anhydride-grafted linear low-density polyethylene as a connecting layer. The interfacial bonding force between the barrier film and the fiber tray is adjusted by a copolymer modifier, and ethylene/vinyl alcohol copolymer is used as the barrier core layer to optimize degradation characteristics.
This design achieves both easy tearing and high barrier properties for the barrier film and fiber tray, ensuring easy separation of materials during recycling and increasing the recycling value of the materials.
Smart Images

Figure CN123025549A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of packaging film recycling technology, specifically to a barrier film for fiber trays, a recycled composite material, and a method for preparing the barrier film. Background Technology
[0002] Fiber-based trays, due to their recyclable and biodegradable environmental properties, are rapidly replacing traditional plastic trays and are widely used in food and industrial product packaging. However, the inherent water vapor, oxygen, and oil barrier properties of fiber materials are insufficient to meet the protection requirements of fresh produce, cooked food, high-oil snacks, and some products requiring moisture protection. Therefore, the industry commonly uses the method of laminating functional barrier films onto the surface of fiber trays to improve their protective capabilities.
[0003] Existing barrier membranes are multi-layered composite materials. While the combination of fiber trays and multi-layered barrier membranes provides excellent barrier performance, it also leads to serious recycling challenges. Clean separation is difficult to achieve during conventional recycling pulping processes, which contradicts the principles of green design. Therefore, how to achieve full recycling and easy separation of fiber trays and surface barrier membranes while ensuring high barrier performance, and ensuring that each material component can enter its respective recycling channel after separation, has become a key technical challenge that urgently needs to be solved in this field. Summary of the Invention
[0004] One of the objectives of this invention is to overcome the deficiencies in the prior art and provide a barrier film for fiber trays. By using a first and second metallocene polyethylene composite as a heat-sealing layer, the mechanical strength and heat-sealing performance of the material can be improved simultaneously. When used in conjunction with a copolymer modifier, the peel strength and tearability between the barrier film and the fiber tray can be effectively balanced, and the degradation characteristics can be optimized. The connecting layer is made of maleic anhydride-grafted linear low-density polyethylene, which can significantly improve the compatibility of the recycled composite material and facilitate subsequent reuse.
[0005] To achieve the above-mentioned process effects, the technical solution of the present invention is as follows: a barrier film for fiber trays, comprising an outer outer layer, a reinforcing composite layer, a first connecting layer, a barrier core layer, a second connecting layer, a transition reinforcing layer and a heat-sealing layer stacked sequentially; The outer outer layer comprises linear low-density polyethylene, first metallocene polyethylene, and low-density polyethylene. The barrier core layer is an ethylene / vinyl alcohol copolymer; Both the first connecting layer and the second connecting layer are maleic anhydride-grafted linear low-density polyethylene. The heat-sealing layer comprises a first metallocene polyethylene, a second metallocene polyethylene, low-density polyethylene, a copolymer modifier, and an opening agent; The copolymer modifier is obtained by grafting hydroxyl-modified polyethylene with ε-caprolactone or with D,L-lactide.
[0006] The preferred technical solution is that, by mass parts, the outer layer comprises 36-42 parts of linear low-density polyethylene, 36-42 parts of first metallocene polyethylene, and 16-22 parts of low-density polyethylene; The heat-sealing layer comprises, by weight, 36-42 parts of first metallocene polyethylene, 33-38 parts of second metallocene polyethylene, 15-20 parts of low-density polyethylene, 3-7 parts of copolymer modifier, and 0.5 parts of opening agent; The first metallocene polyethylene is a high-strength metallocene polyethylene, and the second metallocene polyethylene is a high-thermal-adhesion metallocene polyethylene.
[0007] A preferred technical solution is that the transition reinforcement layer is composed of LLDPE; The reinforcing composite layer includes layers A, B, and C stacked sequentially, with layer A being close to the outermost layer; The composition of layer A includes LLDPE and LDPE in a mass ratio of (66~73):(27~34); The B layer is composed of LDPE; The C layer is composed of LLDPE.
[0008] A preferred technical solution is that the ethylene content in the ethylene / vinyl alcohol copolymer is 30%~34%.
[0009] The preferred technical solution is that the preparation method of the copolymer modifier is as follows: hydroxyl-modified polyethylene and ε-caprolactone in a mass ratio of 1:10 are extruded and purified by a twin-screw extruder at a temperature of 150~155℃ and a speed of 78~82rpm under the action of triethylaluminum catalyst. The second method for preparing the copolymer modifier is as follows: hydroxyl-modified polyethylene and D,L-lactide in a mass ratio of 1:8 are extruded and purified by twin-screw extrusion at a temperature of 150~155℃ and a speed of 78~82rpm under the action of stannous octoate catalyst.
[0010] The preferred technical solution is that the hydroxyl-modified polyethylene is prepared by: polyethylene and 1-(2-hydroxyethyl)-1H-pyrrole-2,5-dione in a mass ratio of 20:1, which are then extruded and purified by a twin-screw extruder at a temperature of 180~185℃ and a speed of 78~82rpm under the action of dicumyl peroxide.
[0011] A preferred technical solution is that the thickness ratio of layer A, layer B, and layer C is (1.5~1.7):(1.5~1.7):1, and the thickness of the reinforcing composite layer accounts for 24%~26% of the total thickness of the barrier film; The thickness of the transition reinforcement layer accounts for 5% to 7% of the total thickness of the barrier film; The outermost layer has a thickness that accounts for 9% to 12% of the total thickness of the barrier film; The thickness of the heat-sealing layer accounts for 28% to 32% of the total thickness of the barrier film; The thickness of the first connecting layer accounts for 6% to 8% of the total thickness of the barrier film; The thickness of the second connecting layer accounts for 6% to 8% of the total thickness of the barrier film; The thickness of the barrier core layer accounts for 13% to 18% of the total thickness of the barrier film; The total thickness of the barrier membrane is 75~150μm.
[0012] The second objective of this invention is to overcome the deficiencies in the prior art and provide a recycled composite material for a barrier membrane. By mass, the recycled composite material comprises 100 parts of recycled material, 3-5 parts of styrene, 1-2 parts of crosslinking agent, and 0.1-0.15 parts of initiator. The recycled material is the pulverized material of the above-mentioned barrier membrane for fiber trays. The crosslinking agent contains double bond groups and ureidopyrimidinone groups.
[0013] A preferred technical solution is that the crosslinking agent is obtained by polymerizing 2-amino-4-hydroxy-6-methylpyrimidine with 1,6-hexanediisocyanate and hydroxyethyl methacrylate, or by polymerizing 2-amino-4-hydroxy-6-methylpyrimidine with isocyanate methacrylate.
[0014] The third objective of this invention is to overcome the deficiencies in the prior art and provide a method for preparing a barrier film for fiber trays. The barrier film is a multilayer co-extruded film. The extrusion feed temperature of the outer layer is 75~215℃, and the extrusion die temperature is 213~217℃. The highest extrusion feed temperature of each layer in the reinforcing composite layer is 75~215℃, and the extrusion die temperature is 213~217℃. The lowest extrusion feed temperature of each layer in the reinforcing composite layer is 75~205℃, and the extrusion die temperature is 20℃. The extrusion feed temperature of the barrier core layer is 100~225℃, and the extrusion die temperature is 223~228℃; the extrusion feed temperature of the transition reinforcement layer is 75~215℃, and the extrusion die temperature is 213~217℃; the extrusion feed temperature of the heat-sealing layer is 75~215℃, and the extrusion die temperature is 213~217℃; the extrusion feed temperature of the first connecting layer and the second connecting layer is 75~235℃, and the extrusion die temperature is 233~237℃.
[0015] The advantages and beneficial effects of this invention are as follows: The heat-sealing layer adopts a composite system of first metallocene polyethylene and second metallocene polyethylene, which can meet the dual requirements of mechanical strength and heat-sealing performance. The introduction of copolymer modifiers effectively harmonizes the interfacial bonding force between the barrier membrane and the fiber tray, ensuring reliable connection while giving it excellent peelability and simultaneously improving the biodegradability of the barrier membrane. By constructing the first and second connecting layers using maleic anhydride-grafted linear low-density polyethylene, the compatibility of multiphase components in the recycled composite material is enhanced, thereby increasing the recycling value of the material. Attached Figure Description
[0016] Figure 1 This is a schematic diagram illustrating the use of the barrier film and fiber tray; Figure 2 This is a diagram showing the peeling of the barrier film. Detailed Implementation
[0017] The specific embodiments of the present invention will be further described below with reference to examples. These examples are only used to more clearly illustrate the technical solutions of the present invention and should not be construed as limiting the scope of protection of the present invention.
[0018] model mLLDPE is manufactured by ExxonMobil and its trade name is 1018MF. mLLDPE is manufactured by Dow, with the trade name AT6202; Low-density polyethylene is manufactured by ExxonMobil and its trade name is 150BW. Low-density polyethylene is manufactured by SABIC, with the trade name HP2025JN; The linear low-density polyethylene is manufactured by Dow, with the trade name 5400G. The adhesive is manufactured by Guangdong Synthetic Materials Technology Co., Ltd., with the trade name HS3-405H3; The ethylene / vinyl alcohol copolymer was produced by Changchun Petrochemical Co., Ltd., with the trade name EV-3251FT; The opening agent is produced by Shanghai Hongwei Plastics Co., Ltd., with the trade name TGN160.
[0019] Copolymer Modifier The copolymer modifier is obtained by grafting hydroxyl-modified polyethylene with ε-caprolactone or with D,L-lactide.
[0020] Furthermore, the polyethylene is HDPE with a melt index of 5~10 g / 10 min. Even further, the polyethylene is HDPE with a melt index of 7~9 g / 10 min.
[0021] Hydroxyl-modified polyethylene uses HDPE as the base material. After grafting, it exhibits high rigidity and strength, improving the barrier properties of the membrane and preventing tearing during the removal of the fiber tray; instead, the membrane tears as a whole. The grafted ε-caprolactone and D,L-lactide are both biodegradable polymers, improving the degradation efficiency of the barrier membrane. Furthermore, the introduction of polar groups creates strong intermolecular interactions with the fiber tray, enhancing the bond strength during heat sealing. During recycling, the maleic anhydride grafted onto linear low-density polyethylene in the first and second connecting layers further improves the compatibility between the polyethylene and the ethylene / vinyl alcohol copolymer of the barrier core layer.
[0022] Method 1 for preparing copolymer modifier: Hydroxyl-modified polyethylene and ε-caprolactone in a mass ratio of 1:10 are reacted with triethylaluminum catalyst (0.5% of the mass of ε-caprolactone) under a nitrogen atmosphere via twin-screw extrusion at a temperature of 150-155℃ and a speed of 78-82 rpm for 4 min. The mixture is then washed with ethanol and purified. Method 2 for preparing copolymer modifier: Hydroxyl-modified polyethylene and D,L-lactide in a mass ratio of 1:8 are reacted with stannous octoate catalyst (the amount of stannous octoate catalyst added is 1% of the mass of D,L-lactide) under a nitrogen atmosphere via twin-screw extrusion at a temperature of 150~155℃ and a speed of 78~82rpm for 12min. The mixture is then washed with ethanol and purified.
[0023] Preparation of hydroxyl-modified polyethylene: Polyethylene (HDPE) and 1-(2-hydroxyethyl)-1H-pyrrole-2,5-dione were mixed at a mass ratio of 20:1 and melt-reactively extruded at 182℃ and 80rpm for 10min under the action of 2% dicumyl peroxide (DCP). The melt-extruded blend was dissolved in toluene and then purified by adding ethanol to obtain the hydroxyl-modified product.
[0024] Crosslinking agent Crosslinking agent L1 is obtained by polymerizing 2-amino-4-hydroxy-6-methylpyrimidine with 1,6-hexamethylene diisocyanate and hydroxyethyl methacrylate. Specifically, 2-amino-4-hydroxy-6-methylpyrimidine and 1,6-hexamethylene diisocyanate are mixed at a molar ratio of 1:6 and reacted at 100°C for 6 hours under a nitrogen atmosphere to obtain a pre-grafted crosslinking agent. The pre-grafted crosslinking agent is then mixed with hydroxyethyl methacrylate at a molar ratio of 1:1.5 and dissolved in chloroform. Under a nitrogen atmosphere, 0.05% (by mass) of dibutyltin dilaurate is added dropwise, and the reaction is carried out at 65°C for 8 hours. After the reaction, the mixture is filtered, washed, and dried.
[0025] Crosslinking agent L2 is obtained by polymerization of 2-amino-4-hydroxy-6-methylpyrimidine and isocyanate methacrylate; wherein, the molar ratio of 2-amino-4-hydroxy-6-methylpyrimidine to isocyanate methacrylate is 1:1.05. First, 2-amino-4-hydroxy-6-methylpyrimidine is dissolved in dimethyl sulfoxide (DMSO), heated to 150°C, and then isoethyl methacrylate is added to react. Subsequently, the mixture is cooled, washed with excess acetonitrile, and dried.
[0026] outer surface The outer layer is composed of linear low-density polyethylene, first metallocene polyethylene and low-density polyethylene.
[0027] Linear low-density polyethylene (LLDPE) offers high tensile strength and puncture resistance, but too much LLDPE affects processing performance, while too little negatively impacts the physical properties of the film. Metallocene polyethylene (mPE), as a toughness enhancer, can further improve the puncture resistance and impact strength of the film in blends, compensating for the shortcomings of single materials. Low-density polyethylene (LDPE) improves the processing flowability of blended materials and helps to improve the transparency and flexibility of the film.
[0028] Barrier Core The barrier core is an ethylene / vinyl alcohol copolymer. Lower ethylene content means a higher proportion of vinyl alcohol segments, stronger intermolecular forces, and a denser structure, resulting in better barrier properties against gases such as oxygen. The EVOH molecular chain contains both polar vinyl alcohol segments and non-polar ethylene segments. Higher ethylene content makes the non-polar characteristics of EVOH more pronounced, increasing its structural similarity to PE and thus improving compatibility. To maintain good barrier performance and compatibility with polyethylene, the ethylene content in the ethylene / vinyl alcohol copolymer is further set at 30%–34%.
[0029] heat seal layer The heat-sealing layer comprises a first metallocene polyethylene, a second metallocene polyethylene, low-density polyethylene, a copolymer modifier, and an opening agent. Furthermore, the first metallocene polyethylene is a high-strength metallocene polyethylene, and the second metallocene polyethylene is a high-thermal-tack-strength metallocene polyethylene. The combination of the first and second metallocene polyethylene simultaneously achieves both mechanical strength and heat-sealing performance. The high strength of the first metallocene polyethylene complements the low-temperature, high-thermal-tack characteristics of the second metallocene polyethylene.
[0030] Furthermore, the thickness of the heat-sealing layer accounts for 28% to 32% of the total thickness of the barrier film; within this range, the thickness can balance good heat-sealing effect and overall film processing performance.
[0031] First connecting layer and second connecting layer Both the first and second connecting layers are maleic anhydride-grafted linear low-density polyethylene.
[0032] The thickness of the first connecting layer accounts for 6% to 8% of the total thickness of the barrier membrane; the thickness of the second connecting layer accounts for 6% to 8% of the total thickness of the barrier membrane.
[0033] The maleic anhydride-grafted linear low-density polyethylene (LLDPE) bonding layer acts as a link between polyethylene and ethylene / vinyl alcohol copolymer materials in the original barrier film. During recycling, it can act as a compatibilizer to repair and strengthen the interfacial bonding between the two materials, thereby improving the tensile strength and toughness of the recycled material.
[0034] Reinforced composite layer The reinforcing composite layer consists of layers A, B, and C stacked sequentially, with layer A being closest to the outermost layer. Layer A is composed of LLDPE and LDPE; layer B is composed of LDPE; and layer C is composed of LLDPE.
[0035] Layer A primarily enhances the mechanical properties of the barrier membrane, such as tensile strength, impact resistance, and puncture resistance. LLDPE and LDPE have the highest crystal orientation, which is beneficial for improving mechanical performance. The addition of LDPE can improve the processability of LLDPE, increase melt strength and extrusion stability, and make the membrane bubble easier to control.
[0036] Layer B primarily enhances the processing stability and cost control of the barrier film, while also improving its transparency and flexibility.
[0037] The C layer, with its symmetrical structure to the transition reinforcement layer, further enhances the mechanical properties of the barrier film, such as tensile strength, impact resistance, and puncture resistance, while also improving processing stability.
[0038] Recycled composite materials The recycled composite material includes recycled material, styrene, a crosslinking agent, and an initiator. The recycled material is pulverized material from the barrier membrane used in fiber trays. The crosslinking agent contains double bond groups and ureidopyrimidinone groups, and the initiator is dicumyl peroxide.
[0039] The working principle between recycled composite materials: Styrene is grafted onto the polyethylene backbone in the recycled material under the action of dicumyl peroxide to form stable free radicals; the crosslinking agent interacts with the free radicals through the double bonds of the acrylate groups, and is also grafted onto the polyethylene backbone. The ureidopyrimidinone groups of the crosslinking agent interact with the hydrogen bonds of the ethylene / vinyl alcohol copolymer, that is, the crosslinking agent improves the compatibility between polyethylene and ethylene / vinyl alcohol copolymer in the recycled material.
[0040] When recycling recycled composite materials, the formation of free radicals during melt extrusion inevitably leads to polymer chain breakage and degradation. To mitigate these adverse effects, styrene copolymerization with crosslinking agents is used as a free radical stabilizing inhibitor, and styrene can improve the thermal stability of recycled composite materials.
[0041] After modification, recycled composite materials can be blended with materials such as polyethylene, polypropylene, PET and nylon, thus enabling the application of recycled composite materials. Among them, the proportion of recycled composite materials is 10% to 35%, which has little impact on the physical properties of the other blend.
[0042] Example 1
[0043] Barrier film (M1): comprising an outer outer layer, a reinforcing composite layer, a first connecting layer, a barrier core layer, a second connecting layer, a transition reinforcing layer, and a heat-sealing layer stacked in sequence.
[0044] By mass, the outer layer consists of 40 parts of LLDPE (5400G), 40 parts of mLLDPE (1018MF), and 20 parts of LDPE (HP2025JN). The reinforcing composite layer comprises layers A, B, and C stacked sequentially. Layer A is located close to the outermost layer and consists of LLDPE (5400G) and LDPE (HP2025JN) in a mass ratio of 70:30. Layer B consists of LDPE (150BW), and layer C consists of LLDPE (5400G). By mass, the heat-sealing layer comprises 40 parts of first mL LDPE (1018MF), 36 parts of second mL LDPE (AT6202), 18.5 parts of LDPE (HP2025JN), 5 parts of copolymer modifier, and 0.5 parts of opening agent; the copolymer modifier is obtained by preparation method one; Both the first and second connecting layers are maleic anhydride-grafted linear low-density polyethylene. The barrier core layer is an ethylene / vinyl alcohol copolymer; The transition reinforcement layer is composed of LLDPE (5400G); The total thickness of the barrier film is 100 μm, the outer layer is 10 μm thick, the A layer in the reinforcing composite layer is 9 μm thick, the B layer is 10 μm thick, the C layer is 6 μm thick, the first connecting layer is 7 μm thick, the barrier core layer is 15 μm thick, the second connecting layer is 7 μm thick, the transition reinforcing layer is 6 μm thick, and the heat-sealing layer is 30 μm thick.
[0045] The barrier film is a multi-layer co-extruded film, extruded through a die. The extrusion temperatures in the co-extrusion equipment, in the following order: feeding section, plasticizing section, homogenizing section, two-stage extrusion section, and die head: Outer layer: 75℃-215℃-215℃-215℃-215℃-215℃; A layer: 75℃-215℃-215℃-215℃-215℃-215℃; Layer B: 75℃-185℃-195℃-205℃-205℃-205℃; Layer C: 75℃-215℃-215℃-215℃-215℃-215℃; First connecting layer: 75℃-235℃-235℃-235℃-235℃-235℃; Barrier core layer: 100℃-215℃-225℃-225℃-225℃-225℃; Second connecting layer: 75℃-235℃-235℃-235℃-235℃-235℃; Transition reinforcement layer: 75℃-215℃-215℃-215℃-215℃-215℃; Heat seal layer: 75℃-215℃-215℃-215℃-215℃-215℃.
[0046] By weight, the barrier membrane recycling composite (N1) comprises 100 parts recycled material, 4 parts styrene, 1.5 parts crosslinking agent, and 0.15 parts initiator. The recycled material is the pulverized material of the aforementioned barrier membrane (M1). The crosslinking agent is 2-amino-4-hydroxy-6-methylpyrimidine obtained by the polymerization reaction of 1,6-hexamethylene diisocyanate and hydroxyethyl methacrylate.
[0047] Preparation of barrier membrane recycling composite material (N1): After the raw materials are mixed, they are fed into the machine through a screw at a speed of 60 rpm. Then the screw speed is increased to 90 rpm, and the mixture is reacted at 200℃ for 10 min. The composite material is then extruded, granulated, and cooled to obtain recycled composite material granules.
[0048] Example 2
[0049] Example 2 is based on Example 1, except that the composition of layer B in the barrier film (M2) is LLDPE (5400G), which is the same as the composition of layer C; the composition of other layers remains unchanged, and the layer thickness also remains unchanged.
[0050] The composition of the barrier membrane recycling composite (N2) remains unchanged, but the recycled material is a pulverized barrier membrane (M2).
[0051] Example 3
[0052] Example 3 is based on Example 1, except that the copolymer modifier for the heat-sealing layer in the barrier film (M3) is obtained by preparation method two, and its composition remains unchanged. The compositions of the other layers remain unchanged, and the layer thicknesses also remain unchanged.
[0053] The composition of the barrier membrane recycling composite (N3) remains unchanged, but the recycled material is a pulverized barrier membrane (M3).
[0054] Example 4
[0055] Example 4 is based on Example 1, except that, by mass parts, the heat-sealing layer in the barrier film (M4) comprises 50 parts of the first mLLDPE (1018MF), 26 parts of the second mLLDPE (AT6202), 18.5 parts of LDPE (HP2025JN), 5 parts of copolymer modifier, and 0.5 parts of opening agent. The components of other layers remain unchanged, as does the layer thickness.
[0056] The composition of the barrier membrane recycling composite (N4) remains unchanged, but the recycled material is a pulverized barrier membrane (M4).
[0057] Example 5
[0058] Example 5 is based on Example 1, except that, by mass parts, the heat-sealing layer in the barrier film (M5) comprises 36 parts of the first mLLDPE (1018MF), 36 parts of the second mLLDPE (AT6202), 18.5 parts of LDPE (HP2025JN), 9 parts of copolymer modifier, and 0.5 parts of opening agent. The components of other layers remain unchanged, as does the layer thickness.
[0059] The composition of the barrier membrane recycling composite (N5) remains unchanged, but the recycled material is a pulverized barrier membrane (M5).
[0060] Example 6
[0061] Example 6 is based on Example 1, except that, by mass parts, the heat-sealing layer in the barrier film (M6) comprises 40 parts of the first mLLDPE (1018MF), 40 parts of the second mLLDPE (AT6202), 18.5 parts of LDPE (HP2025JN), 1 part of copolymer modifier, and 0.5 parts of opening agent. The components of other layers remain unchanged, as does the layer thickness.
[0062] The composition of the barrier membrane recycling composite (N6) remains unchanged, but the recycled material is a pulverized barrier membrane (M6).
[0063] Example 7
[0064] Example 7 is based on Example 1, except that the barrier core layer of the barrier film (M7) has a thickness of 18 μm, the outer layer has a thickness of 9 μm, and the heat-sealing layer has a thickness of 28 μm; the thicknesses of the other layers remain unchanged. The composition of each layer remains unchanged.
[0065] The composition of the barrier membrane recycling composite (N7) remains unchanged, but the recycled material is a pulverized barrier membrane (M7).
[0066] Example 8
[0067] Example 8 is based on Example 1, except that the barrier membrane recycled composite material (N8) includes 100 parts of recycled material, 2 parts of styrene, 1.5 parts of crosslinking agent and 0.15 parts of initiator, and the recycled material is the pulverized material of the above barrier membrane (M1).
[0068] Example 9
[0069] Example 9 is based on Example 1, except that the barrier membrane recycled composite material (N9) includes 100 parts of recycled material, 1.5 parts of crosslinking agent and 0.15 parts of initiator, and does not contain styrene. The recycled material is the pulverized material of the above-mentioned barrier membrane (M1).
[0070] Example 10
[0071] Example 10 is based on Example 1, except that the barrier membrane recycled composite material (N10) includes 100 parts of recycled material, 4 parts of styrene and 0.15 parts of initiator, and does not contain crosslinking agent. The recycled material is the pulverized material of the above barrier membrane (M1).
[0072] Example 11
[0073] Example 11 is based on Example 1, except that the barrier membrane recycled composite material (N11) is only recycled material and does not contain crosslinking agent and styrene for grafting. The recycled material is the pulverized material of the above barrier membrane (M1).
[0074] Comparative Example 1 The comparative example is based on Example 1, except that, by mass parts, the heat-sealing layer of the barrier film (M8) comprises 40 parts of first mLLDPE (1018MF), 40 parts of second mLLDPE (AT6202), 19.5 parts of LDPE (HP2025JN), and 0.5 parts of opening agent, and does not contain a copolymer modifier. The composition of other layers remains unchanged, as does the layer thickness.
[0075] The composition of the barrier membrane recycling composite (N12) remains unchanged, but the recycled material is a pulverized barrier membrane (M8).
[0076] Performance testing of barrier film samples in the examples and comparative examples: 1. Tensile strength: Determined according to standard GB / T 1040.3-2006; 2. Elongation at break: Measured according to standard GB / T 1040.3-2006; 3. Oxygen permeability: Measured according to standard GB / T1038-2000; 4. Peel strength: Measured according to standard GB / T 8808; 5. Puncture resistance: Tested according to standard GB / T 37841; puncture test was conducted using a 1mm needle at a speed of 60mm / min.
[0077] The performance test results of the barrier films in the examples and comparative examples are as follows:
[0078] Compared to Example 1, in Example 2, the composition of layer B is LLDPE instead of LDPE. Although this improves the mechanical properties of the barrier film, the transparency and flexibility of the barrier film decrease.
[0079] Compared to Example 1, Example 3 uses a copolymer modifier obtained through a grafting reaction of hydroxyl-modified polyethylene with D,L-lactide. This copolymer modifier exhibits higher rigidity, resulting in increased tensile strength of the barrier membrane, but decreased elongation at break. If the barrier membrane is recycled and not reused, but instead undergoes degradation, the biodegradation rate is relatively slow. Therefore, the copolymer modifier obtained through Method 1 (ε-caprolactone grafted with hydroxyl modification) has a faster biodegradation rate.
[0080] Compared to Example 1, Example 4 shows an increase in the content of the first metallocene polyethylene (high-strength metallocene polyethylene) and a decrease in the content of the second metallocene polyethylene (high-heat-tack metallocene polyethylene) in the heat-sealing layer. Although this can improve the mechanical properties of the barrier film, the adhesion to the fiber tray decreases after heat sealing.
[0081] Compared to Example 1, Example 5 shows that although the content of the first metallocene polyethylene in the heat-sealing layer is reduced, the content of the copolymer modifier is increased. The impact on mechanical properties is small, but the barrier properties are improved. Moreover, the adhesion to the fiber tray is increased, which is not conducive to the peeling of the barrier film and also increases the processing difficulty of the heat-sealing layer.
[0082] Compared to Example 1, Example 6 has too little content of copolymer modifier in the heat-sealing layer, which has a negative impact on the barrier performance and degradation rate of the barrier film.
[0083] Compared to Example 1, Example 7 shows that the thickness of the barrier core layer is increased, improving the barrier performance. However, while keeping the total thickness of the barrier film constant, the thickness of the puncture-resistant outer layer and the heat-sealing layer is reduced, resulting in a decrease in both the mechanical properties and puncture resistance of the barrier film, and the barrier film becomes harder.
[0084] Performance testing of recycled composite materials in examples and comparative cases: 1. Tensile strength: Determined according to standard GB / T 1040.2; 2. Elongation at break: Measured according to standard GB / T 1040.2.
[0085] The performance test results of the recycled composite materials in the examples and comparative examples are as follows:
[0086] Compared to Example 1, Example 8 shows a reduction in the styrene content in the barrier membrane recycling composite, which has a negative impact on the mechanical properties of the recycling composite.
[0087] Compared to Example 1, Example 10 did not contain a crosslinking agent in the barrier membrane recycling composite, resulting in decreased compatibility of the recycled material and a decrease in the mechanical properties of the recycled composite.
[0088] Compared to Example 1, Comparative Example 1 has an increased LDPE content in the heat-sealing layer and does not contain a copolymer modifier, which has a negative impact on the mechanical properties of the recycled composite material.
[0089] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the technical principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A barrier film for fiber trays, characterized in that, It includes an outer layer, a reinforcing composite layer, a first connecting layer, a barrier core layer, a second connecting layer, a transition reinforcing layer, and a heat-sealing layer, which are stacked in sequence. The outer outer layer comprises linear low-density polyethylene, first metallocene polyethylene, and low-density polyethylene. The barrier core layer is an ethylene / vinyl alcohol copolymer; Both the first connecting layer and the second connecting layer are maleic anhydride-grafted linear low-density polyethylene. The heat-sealing layer comprises a first metallocene polyethylene, a second metallocene polyethylene, low-density polyethylene, a copolymer modifier, and an opening agent; The copolymer modifier is obtained by grafting hydroxyl-modified polyethylene with ε-caprolactone or with D,L-lactide.
2. The barrier film for fiber trays according to claim 1, characterized in that, By mass fractions, the outer layer comprises 36-42 parts of linear low-density polyethylene, 36-42 parts of first metallocene polyethylene and 16-22 parts of low-density polyethylene; The heat-sealing layer comprises, by weight, 36-42 parts of first metallocene polyethylene, 33-38 parts of second metallocene polyethylene, 15-20 parts of low-density polyethylene, 3-7 parts of copolymer modifier, and 0.5 parts of opening agent; The first metallocene polyethylene is a high-strength metallocene polyethylene, and the second metallocene polyethylene is a high-thermal-adhesion metallocene polyethylene.
3. The barrier film for fiber trays according to claim 1 or 2, characterized in that, The transition reinforcement layer is composed of LLDPE; The reinforcing composite layer includes layers A, B, and C stacked sequentially, with layer A being close to the outermost layer; The composition of layer A includes LLDPE and LDPE in a mass ratio of (66~73):(27~34); The B layer is composed of LDPE; The C layer is composed of LLDPE.
4. The barrier film for fiber trays according to claim 1, characterized in that, The ethylene / vinyl alcohol copolymer contains 30% to 34% ethylene.
5. The barrier film for fiber trays according to claim 1, characterized in that, The preparation method of the copolymer modifier is as follows: hydroxyl-modified polyethylene and ε-caprolactone in a mass ratio of 1:10 are extruded and purified by a twin-screw extruder at a temperature of 150~155℃ and a speed of 78~82rpm under the action of triethylaluminum catalyst. The second method for preparing the copolymer modifier is as follows: hydroxyl-modified polyethylene and D,L-lactide in a mass ratio of 1:8 are extruded and purified by twin-screw extrusion at a temperature of 150~155℃ and a speed of 78~82rpm under the action of stannous octoate catalyst.
6. The barrier film for fiber trays according to claim 5, characterized in that, Preparation of the hydroxyl-modified polyethylene: polyethylene and 1-(2-hydroxyethyl)-1H-pyrrole-2,5-dione in a mass ratio of 20:1 were extruded and purified by a twin-screw extruder at a temperature of 180~185℃ and a speed of 78~82rpm under the action of dicumyl peroxide.
7. The barrier film for fiber trays according to claim 3, characterized in that, The thickness ratio of layer A, layer B, and layer C is (1.5~1.7):(1.5~1.7):1, and the thickness of the reinforcing composite layer accounts for 24%~26% of the total thickness of the barrier film. The thickness of the transition reinforcement layer accounts for 5% to 7% of the total thickness of the barrier film; The outermost layer has a thickness that accounts for 9% to 12% of the total thickness of the barrier film; The thickness of the heat-sealing layer accounts for 28% to 32% of the total thickness of the barrier film; The thickness of the first connecting layer accounts for 6% to 8% of the total thickness of the barrier film; The thickness of the second connecting layer accounts for 6% to 8% of the total thickness of the barrier film; The thickness of the barrier core layer accounts for 13% to 18% of the total thickness of the barrier film; The total thickness of the barrier membrane is 75~150μm.
8. A recycled composite material for a barrier membrane, characterized in that, By mass fraction, the recycled composite material comprises 100 parts recycled material, 3-5 parts styrene, 1-2 parts crosslinking agent and 0.1-0.15 parts initiator. The recycled material is the pulverized material of the fiber tray barrier membrane according to any one of claims 1-7. The crosslinking agent contains double bond groups and ureidopyrimidinone groups.
9. The recyclable composite material of the barrier membrane according to claim 8, characterized in that, The crosslinking agent is obtained by polymerizing 2-amino-4-hydroxy-6-methylpyrimidine with 1,6-hexamethylene diisocyanate and hydroxyethyl methacrylate, or by polymerizing 2-amino-4-hydroxy-6-methylpyrimidine with isocyanate methacrylate.
10. A method for preparing a barrier film for a fiber tray, characterized in that, The barrier film is a multilayer co-extruded film. The extrusion feed temperature of the outer layer is 75~215℃, and the extrusion die temperature is 213~217℃. The highest extrusion feed temperature of each layer in the reinforcing composite layer is 75~215℃, and the extrusion die temperature is 213~217℃. The lowest extrusion feed temperature of each layer in the reinforcing composite layer is 75~205℃, and the extrusion die temperature is 203~207℃. The extrusion feed temperature of the barrier core layer is 100~225℃, and the extrusion die temperature is 223~228℃. The extrusion feed temperature of the transition reinforcing layer is 75~215℃, and the extrusion die temperature is 213~217℃. The extrusion feed temperature of the heat-sealing layer is 75~215℃, and the extrusion die temperature is 213~217℃. The extrusion feed temperature of the first connecting layer and the second connecting layer is 75~235℃, and the extrusion die temperature is 233~237℃.
